2018
DOI: 10.3892/ijo.2018.4384
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PLIN2 is a prognostic marker and attenuates tumor progression in clear cell renal cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common renal malignancy in adults, the incidence of which continues to increase. The lipid droplet protein perilipin 2 (PLIN2), which was originally considered an RNA transcript, is markedly expressed during adipocyte differentiation. In addition, it has been observed to be elevated in numerous types of cancer, including ccRCC; however, its essential function remains unclear in ccRCC. The present study examined the expression of PLIN2 in ccRCC, and aimed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 44 publications
1
56
3
Order By: Relevance
“…Overexpression of PLIN2 has been observed in many diseases with LD accumulation. 41 In our study, data from real-time PCR showed a decrease in the mRNA level of PLIN2 after 48 hours of oxLDL treatment; however, in the same experimental group the level of PLIN2 protein was elevated.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Overexpression of PLIN2 has been observed in many diseases with LD accumulation. 41 In our study, data from real-time PCR showed a decrease in the mRNA level of PLIN2 after 48 hours of oxLDL treatment; however, in the same experimental group the level of PLIN2 protein was elevated.…”
Section: Discussioncontrasting
confidence: 40%
“…Interestingly, we only observed that oxLDL inhibited lipophagy by suppressing LD‐lysosome fusion and lysosomal biogenesis but not increasing lysosomal destabilization in VSMCs. Overexpression of PLIN2 has been observed in many diseases with LD accumulation . In our study, data from real‐time PCR showed a decrease in the mRNA level of PLIN2 after 48 hours of oxLDL treatment; however, in the same experimental group the level of PLIN2 protein was elevated.…”
Section: Discussionsupporting
confidence: 40%
“…IHC was conducted as described previously (15). Tissues were sequentially fixed in formalin, dehydrated, and embedded in paraffin.…”
Section: Ihc and Immunofluorescencementioning
confidence: 99%
“…120 As described here, although several studies reported the impact of AQP-1 and PLIN2 in RCC on early detection, others showed the association of the expression of these molecules with the prognosis of advanced RCC. 121,122 Based on these reports, AQP-1 and PLIN2 are expected to be clinically useful biomarkers for RCC both in early and advanced stages in the future.…”
Section: Aqp-1 and Plin2mentioning
confidence: 99%